ACTIVATING STUDENTS’ SPEAKING ABILITY IN ASKING AND GIVING OPINION BY USING QUALITY QUESTIONING STRATEGY FOR SENIOR HIGH SCHOOL STUDENTS - Addinu Rahmah; Aryuliva Adnan (Universitas Negeri Padang, 2017)
Teaching process in speaking English is really difficult for some teacher in Senior High School, especially in Asking and Giving Opinion. Unparticipation from students during teaching speaking become major problem to solve. Also, the monotonous teaching speaking which focuses through theory and books make students and teacher having less interction. According to these problems, writer will use the strategy to deal with those problems. So that, students could activate their speaking ability in speakingclass, especially in Asking and Giving opinion. Strategy that writer will use is Quality Questioning Strategy. Quality Questioning Strategy is the questions selected by the teacher to stimulate students thinking outcomes in activate students’ speaking ability. The questions should be an easy questions contains several familiar vocabularies by the students. Thus, there are some rules in using this strategy as follow: Ask Question, Wait Time, No Hands- Up, dan Response. In applying Quality Questioning, teacher needs to follow those rules beacuse the process of those rules will stimulate students thinking outcomes in speaking class, especially in asking and Giving Opinion. Writer hopes that this strategy will activate students speaking ability, especially in Asking and Giving Opinion.